(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Large sections of planners and policy makers in the country have argued that there exists no serious problem of infrastructural deficiency that cannot be tackled through management solutions. All that is needed is to restructure the system of governance, legal and administrative framework in a manner that the standard reform measures can be implemented. Reduction of public sector intervention, ensuring appropriate prices for infrastructure and civic amenities through elimination or reduction of subsidies, development of capital market for resource mobilisation, facilitating private and joint sector projects, simplification of legislative system to bring about appropriate land use changes and location of economic activities etc. are being advocated as the remedial package (World Bank 1995, Expert Group on Commercialization of Infrastructure 1996, World Bank 1998).